2022
DOI: 10.1098/rsos.191456
|View full text |Cite
|
Sign up to set email alerts
|

The ontogeny of children's social emotions in response to (un)fairness

Abstract: Humans have a deeply rooted sense of fairness, but its emotional foundation in early ontogeny remains poorly understood. Here, we asked if and when 4- to 10-year-old children show negative social emotions, such as shame or guilt, in response to advantageous unfairness expressed through a lowered body posture (measured using a Kinect depth sensor imaging camera). We found that older, but not younger children, showed more negative emotions, i.e. a reduced upper body posture, after uninten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 90 publications
0
4
0
Order By: Relevance
“…Importantly, it is not children’s elevated posture per se that reflected positive emotions but rather the direction of the effects was such that positive outcomes, which are generally associated with positive emotions, resulted in elevated body posture. In contrast, negative events such as failing to achieve a goal 42 , 58 , receiving undeserving rewards 51 , 59 , or making unjustified requests for help 52 resulted in lowered body posture.…”
Section: Discussionmentioning
confidence: 96%
“…Importantly, it is not children’s elevated posture per se that reflected positive emotions but rather the direction of the effects was such that positive outcomes, which are generally associated with positive emotions, resulted in elevated body posture. In contrast, negative events such as failing to achieve a goal 42 , 58 , receiving undeserving rewards 51 , 59 , or making unjustified requests for help 52 resulted in lowered body posture.…”
Section: Discussionmentioning
confidence: 96%
“…The research from both primatology and developmental psychology support an understanding of fairness not as a value, but as a biological adaptation. H. sapiens possess the homeostatic expectation to be treated fairly (Gerdemann et al, 2022;Bjorklund, 2020). The essence of this handbook chapter concerns the potential negative impact of (in)justice on worker health and safety.…”
Section: Fairness As a Biological Adaptationmentioning
confidence: 99%
“…The most systematic investigation to date of changes in children's body posture in the context of (un)fairness demonstrated that between 4 and 10 years of age, children's emotions expressed in response to receiving more of a reward than a peer (i.e., advantageously unequal outcomes) became more negative with increasing age. Conversely, children's emotions became more positive with age following equal distributions of resources (Gerdemann, McAuliffe, Blake, Haun, & Hepach, 2022a). Together, these findings suggest that emotions can regulate children's cooperative interactions although more research is needed to specify this relation.…”
Section: Fear Can Promote Competition Defensive Aggression and Domina...mentioning
confidence: 99%